Effect of Vitamin D Analogue on Rosuvastatin-Induced Myopathy in Wistar Rats - Bharti Chogtu; Balaji Ommurugan; Sereen R. Thomson; Sneha G. Kalthur (The Scientific World Journal)
Objectives. Statin-induced myopathy is one of the major causes of poor adherence and discontinuation of this medication. There are contrary results regarding association of vitamin D insufficiency with statin-induced myopathy. This study was done to determine the effect of the vitamin D3 analogue alfacalcidol on Rosuvastatin-induced myopathy in rats. Methodology. Animals were divided into six groups with 6 rats in each group. Groups I and II acted as controls, Group III and Group IV were administered Rosuvastatin 120 mg/kg/day and 160 mg/kg/day, Groups V and VI were administered alfacalcidol 0.1 μg/kg/day in addition to Rosuvastatin 120 mg/kg/day and 160 mg/kg/day, respectively. All drugs were administered orally for 15 days. Plasma creatine kinase (CK) levels were estimated on day 10 and day 15. Animals were sacrificed and muscles were sent for histopathological examination. Results. On day 10, Groups V and VI showed a statistically significant increase in plasma CK levels as compared to the control (p<0.001) and were significantly lower (p<0.001) as compared to Groups III and IV, respectively. However, on day 15, plasma CK levels in Groups V and VI were comparable to those of control groups with a nonsignificant difference (p>0.05). On comparing the histology, Groups V and VI showed a significant difference as compared to statin-only groups (Groups III and IV) as there were signs of regeneration, less splitting, and fragmentation of muscle fibres. Conclusion. The present study shows that the vitamin D analogue alfacalcidol prevents statin-induced myopathy. The serum CK levels are comparable to the control group on day 15 of vitamin D administration.